1991
DOI: 10.1148/radiology.178.3.1994431
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the knee after arthroscopic surgery: diagnosis with MR imaging.

Abstract: Spontaneous osteonecrosis about the knee typically is a disease of the elderly characterized by an acute onset of pain. The exact cause of this condition has long been debated, although a causative relationship between meniscal tears and spontaneous osteonecrosis about the knee has been postulated. Seven patients with knee pain, meniscal tears, and chondromalacia without initial evidence of osteonecrosis at magnetic resonance (MR) imaging underwent arthroscopic surgery with meniscal recontouring or repair and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(59 citation statements)
references
References 0 publications
1
53
0
5
Order By: Relevance
“…Fat suppression in T2-weighted images presents a typical zone of high signal intensity (bone marrow edema) with a low signal intensity area in the lesion's center. These findings are similar to femoral condyle necrosis [1,2,5].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Fat suppression in T2-weighted images presents a typical zone of high signal intensity (bone marrow edema) with a low signal intensity area in the lesion's center. These findings are similar to femoral condyle necrosis [1,2,5].…”
Section: Discussionsupporting
confidence: 81%
“…The histological findings of Narváez et al [14] suggest that the etiology of spontaneous osteonecrosis results from an insufficient subchondral fracture in an osteoporotic bone [8]. Spontaneous necrosis of the knee is also described as an arthroscopy complication [2,5,18].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology remains unclear, but the localized vascular insuffi ciency may explain subchondral osteonecrosis due to disruption of the nutrition supply to the cartilage above [ 33 ]. Spontaneous osteonecrosis of the knee has been also described as a complication after arthroscopic repair of the meniscal tears, and the lesion may be a late sequela of meniscal injury in association with cartilage defects and arthroscopic surgery [ 34 ]. Secondary osteonecrosis is caused by a number of well-recognized predisposing factors for osteonecrosis (e.g., systemic lupus erythematosus, steroid use, pancreatitis, alcoholism, HIV infection and renal transplants) or may be secondary to an old trauma [ 35 ].…”
Section: Osteonecrosis Of the Subchondral Bonementioning
confidence: 99%
“…Recent publications report osteonecrosis of the knee following arthroscopic surgery. Muscolo et al [23] reported eight cases, Brahme et al [5] seven cases and Santori et al [28] two cases. Three articles describe several cases of osteonecrosis after laser-assisted arthroscopic surgery [10,12,27].…”
Section: Introductionmentioning
confidence: 97%